In situ oxygen microelectrode measurements of bottom-ice algal production in McMurdo Sound, Antarctica - Trenerry, LJ; McMinn, A; Ryan, KG (Polar Biology, 2002)
In-situ estimates of fast-ice algal productivity at Cape Evans, McMurdo Sound, in 1999 were lower than at the same site in previous years. Under-ice irradiance was between 0 and 8 mol photons m-2 s-1; the ice was between 1.9 and 2.0 m thick and the algal biomass averaged 150 mg chl a m-2, although values as high as 378 mg chl a m-2 were recorded. Production on 11 and 12 November was between 0.053 and 1.474 mg C m-2 h-1. When the data from 11 November were fitted to a hyperbolic tangent function, a multilinear regression gave estimates for Pmax of 0.571 nmol O2 cm-2 s-1, an of 0.167 nmol O2 cm-2 s-1 mol-1 photons m-2 s-1 and an Ek of 3.419 mol photons m-2 s-1. A Pmax of 2.674 nmol O2 cm-2 s-1, an of 0.275 nmol O2 cm-2 s-1 mol-1 photons m-2 s-1, r of 0.305 nmol O2 cm-2 s-1 and an Ek of 9.724 mol-1 photons m-2 s-1were estimated from the 12 November data. The sea-ice algal community was principally comprised of Nitzschia stellata, Entomoneis kjellmanii and Berkeleya adeliensis. Other taxa present included N. lecointei, Fragilariopsis spp., Navicula glaciei, Pleurosigma spp. and Amphora spp. Variations in the method for estimating the thickness of the diffusive boundary layer were not found to significantly affect the measurements of oxygen flux. However, the inability to accurately measure fine-scale variations in biomass is thought to contribute to the scatter of the P versus E data.